Task-Centered Instruction With Hard and Soft Scaffolding to Empower Academic Self-Efficacy and Creativity - Mashfufah, Aynin; Faizah, Siti; Rufiana, Intan Sari; Ekawati, Ratna; Mariani, Sijah; Wicaksono, Adyatma Nugrahsanto (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to empower students' academic confidence and creativity through task-centered instruction. The research method used is ADDIE with a pre-experimental design (posttest-only design). The research subjects involved were 26 fourth-grade elementary school students in Blitar City. The instruments used were a questionnaire to measure academic self-efficacy, which had been developed from previous research, and a rubric for assessing student creativity. The data were analyzed descriptively and quantitatively and classified into five categories (excellent, good, fair, poor, and very poor). The results of the data analysis showed that the students' academic confidence was, on average, in the good category. Student creativity tended to vary from very good, good, fair, and poor. Classically, student creativity was quite good. This study shows that guidance needs to be provided appropriately to support student learning progress, especially to support confidence, so that students are motivated to learn. The results of this study still need to be followed up by researching a larger sample and using an experimental method by comparing the experimental class and the control class. Then, the relationship between academic self-efficacy and the level of student creativity and how it affects learning outcomes needs to be studied.